The Mix of Accountancy Policy and Tax Strategy in Company’s Financial Result - Rafał Marciniak (Contemporary Economics)
The use of legally possible accountancy methods may influence entrepreneurs’ real economic situation as well as their ability to perform in the future. This article presents an introduction to the problems of decision dilemmas in the area of balance law. A future result-oriented approach to the accountancy policy requires devising a method which would help choose an optimal variant among the least risky ones. Since a choice dilemma deals with future and uncertain events, it is necessary to apply statistical analysis with its rules of inference. Because of the changing environment, this issue poses a complex decision problem in conditions of uncertainty. It, therefore, means that the rules of probability theory need to be used in the inference process. With subjective probability it is then possible to calculate the value of expected profits and define the risk of the variants within the discussed accountancy policy.